Nursing Process implementation in a gerontogeriatric context: qualitative research - Francine Casarin; Juliana Silveira Colomé; Liliane Alves Pereira; Emanuelli Mancio Ferreira da Luz; Oclaris Lopes Munhoz; Silomar Ilha (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: to describe Nursing Process implementation in a faith-based senior living community. Method: strategic action research with 19 nursing professionals and three managers of a faith-based senior living community. Implementation took place in four phases: diagnosis, planning, implementation and assessment. The data collected through semi-structured interviews and focus groups were subjected to discursive textual analysis. Results: the central categories were constructed: Nursing Process in faith-based senior living community: diagnosis of knowledge and application; Nursing Process in faith-based senior living community: implementation; Nursing process in faith-based senior living community: assessment after its implementation. Conclusion: Nursing Process implementation made it possible to structure work management/organization, contributing to knowledge, organization and continuity of care for safety and professional support.